The development of inclusive education with regard to teacher competencies: Current situation, problems and perspectives - Jablan Branka Đ.; Maksimović Jasna M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2020)
This paper aims to point out the importance of acquiring and developing teacher competencies for work with children with disabilities in an inclusive educational environment. After providing an overview of educational inclusion as the goal and content of current reform processes both in Serbia and around the world, the paper examines this process from the standpoint of teachers and their inclusion competencies. An insight into different studies and research results on teachers' roles, attitudes and competencies indicates that educational inclusion in our country has not taken hold to a sufficient extent, and that teachers express serious doubts regarding their competencies to work with children from sensitive social groups. In practice, teachers, as well as students of teacher education faculties are not sufficiently familiar with the fundamental principles of the inclusive approach to education, and emphasize that they are more ready to work with children with mild disabilities. On the other hand, they are of the opinion that children with multiple disabilities should be educated in specialized institutions. In conclusion, the development of the concept and practice of inclusive education will require serious interventions, both in terms of initial teacher education, and in terms of promoting their role in the contemporary education system for children with disabilities.